2002
DOI: 10.4319/lo.2002.47.1.0142
|View full text |Cite
|
Sign up to set email alerts
|

Grazing rates of bacterivorous protists inhabiting diverse marine planktonic microenvironments

Abstract: Bacterivory on aggregates and bulk seawater by three nanoflagellates and a microciliate was investigated. A new approach to measure bacterivory on the attached bacterial community is proposed. Macroaggregates containing attached fluorescently labeled bacteria (FLB) were obtained by adding labeled planktonic bacteria to rolling tanks filled with natural seawater, and they were used to measure protistan grazing rates on the bacteria attached to aggregates. Protistan grazing on free-suspended bacteria was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…In contrast, both small and large heterotrophic dinoflagellates declined rapidly with depth. We also observed that a number of the smaller flagellates, especially among the kinetoplastidae, appeared to be associated with (marine snow) aggregates, an observation consistent with other studies (Artolozaga et al 2002, Kiørboe et al 2004. Among the HNF genera, especially in bathypelagic waters, smaller unidentified species became increasingly important, as has also been reported elsewhere (Arndt et al 2003.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, both small and large heterotrophic dinoflagellates declined rapidly with depth. We also observed that a number of the smaller flagellates, especially among the kinetoplastidae, appeared to be associated with (marine snow) aggregates, an observation consistent with other studies (Artolozaga et al 2002, Kiørboe et al 2004. Among the HNF genera, especially in bathypelagic waters, smaller unidentified species became increasingly important, as has also been reported elsewhere (Arndt et al 2003.…”
supporting
confidence: 91%
“…Similarly, the larger heterotrophic (and mixotrophic) dinoflagellates known to be capable of grazing larger prey also declined rapidly with depth. The loss of these populations was directly associated with the decline of phytoplankton prey, while smaller HNF and oligotrichs have a greater affinity for bacterial and detrital material and are known to colonise descending aggregates (Artolozaga et al 2002, Kiørboe et al 2004. Spatial changes in composition related to epipelagic waters only occurred in the upper mesopelagic zone; beyond these depths, due to the in creasing importance of small unidentified HNF, we were unable to identify clear changes in terms of speciation.…”
Section: Deep Water Microzooplankton Assemblagesmentioning
confidence: 79%
“…The size-specific abundance of flagellates showed the strongest decrease with increasing aggregate size, whereas that of ciliates decreased less. The grazing rates of protists were calculated using the relationships between bacteria and protozoa abundance to estimate grazing rates of protozoa (Artolozaga et al 2002). The average cell-specific grazing rate of protists was 2.8 ± 1.9 bacteria flagellate , whereas the fraction of free-living bacteria grazed was 27 ± 18% d -1…”
Section: Microbial Colonizationmentioning
confidence: 99%
“…In an inter-ecosystem comparison, Sanders et al (1992) found a strong correlation between specific community bacterivory and bacterial production as well as bacterial numbers. Considering the high densities of attached bacteria relative to that in the surrounding water, grazing rates of bacterivorous protists on these have previously been shown to be surprisingly low compared to those on free-living bacteria (Artolozaga et al 2002). Low grazing rates of aggregate-associated protists, however, may partly be compensated by the higher cell-specific biomass and nutrient content of aggregate-associated microorganisms .…”
Section: Colonization Patternmentioning
confidence: 99%
“…data). Despite this evidence for its importance, quantification of grazing mortality of marine snow bacteria is rare (Caron 1987, Lawrence & Snyder 1998, Riemann et al 2000, Artolozaga et al 2002, 2004.…”
Section: Introductionmentioning
confidence: 99%